Towards value pluralism, knowledge pluralism, and recognitional justice: improving integration of cultural benefits of ecosystem services in environmental decision-making - Hoelting, Kristin R., author; Gavin, Michael C., advisor; Martinez, Doreen E., committee member; Schuster, Rudy M., committee member; Schultz, Courtney A., committee member (Colorado State University. Libraries, 2022)
This mainstreaming of the ecosystem services (ES) concept and approach is reflected in its adoption by governments and non-governmental organizations around the world, including in the United States: in 2015, a U.S. Federal Memorandum directed all Federal agencies to integrate ES information in their decision-making processes. In principle this momentum represents an opportunity for improved consideration of the cultural benefits of ES in decision-making, as part of the improved consideration of ES as a whole. However, there is concern that cultural benefits – and the plural values and multiple knowledge systems they reveal – are being left behind in processes of standardization in ES theory and practice. Cultural benefits challenge the emphasis on instrumental values common in the ES field. Further, in revealing the culturally contextual and situated character of all ES, cultural benefits challenge the universalizing and generalizing tendencies common in this field. More meaningful consideration of the cultural benefits of ES, as one strand of a larger movement toward value pluralism and knowledge pluralism, is a question of both equity and ecological outcomes. On-going conversations and critiques in the ES field around how to create space for multiple worldviews, including multiple human-nature relationships and well-beings, are critical to bringing environmental management into alignment with environmental justice, including distributional, procedural, and recognitional justice for current and future generations. In addition, ensuring a place for currently marginalized knowledge systems in ES theory and practice, including place-based and Indigenous ways of knowing, brings new solutions to the table and increases the adaptive capacity of managers and decision-makers at local and global scales as they face into growing global environmental challenges. To support movement toward knowledge pluralism in ES theory and practice, the three manuscripts presented in this dissertation offer: 1) a conceptual framework that reveals ES-knowledge as a system, seeking to support personal and collective reflexivity around the role of worldviews embedded in our institutions and the implications of this (Manuscript 1); 2) a theoretical model of learning opportunities for integration of a diverse forms of knowledge, and explores how some cultural-benefits-knowledge-forms are more likely to convey non-instrumental, relational value aspects or holistic value perspectives, and more likely to be effectively considered at particular stages of decision-making (Manuscript 2); and 3) an Opportunities Framework that can be used to systematically identify available forms of cultural-benefits-knowledge, and the opportunities that exist to integrate these knowledge forms in a particular decision context (Manuscript 3). This final manuscript both introduces the framework and illustrates its potential by applying it to a past decision process: Elwha River dam removal and restoration in Washington State, U.S.A. Next steps for research and application of a knowledge-pluralist ES approach are discussed in the dissertation's conclusion.
Keywords: ecosystem services; recognition justice; value pluralism; knowledge pluralism; cultural benefits; recognitional justice